К вопросу об истории преподавания славянских языковедческих дисциплин в старом Вильнюсском университете - Каупуж, А. (Kalbotyra, 1972)
According to the book of reports of Literature and Free Arts department in the Vilnius University prof. Loboiko still in the year of 1824 began to read a short course in comparative grammar of Russian, Polish and Old Slavonic languages. It was one of he first attempts of reading such a course not only in the universities of Russian Empire but in the universities of West countries as well. In his lectures prof. Loboiko had been using his competitive work and the manuscript which had been preserved in Leningrad Institute of Russian Literature. In the article the author presents in short the content, of Loboiko’s work and comes to the conclusion that Loboiko being well acquainted with the scientific literature of his time could arouse students’ interest in Slavonic languages.